A case report of NPHP1 deletion in Chinese twins with nephronophthisis - Feng Chen; Limeng Dai; Jun Zhang; Furong Li; Jinbo Cheng; Jinghong Zhao; Bo Zhang (BMC, 2020)
Abstract Background Nephronophthisis (NPHP) is a rare autosomal recessive inherited disorder with high heterogeneity. The majority of NPHP patients progress to end-stage renal disease (ESRD) within the first three decades of life. As an inherited disorder with highly genetic heterogeneity and clinical presentations, NPHP still poses a challenging task for nephrologists without special training to make a well-judged decision on its precise diagnosis, let alone its mechanism and optimal therapy. Case presentation A Chinese family with NPHP was recruited in current study. The clinical characteristics (including findings from renal biopsy) of NPHP patients were collected from medical records and the potential responsible genes were explored by the whole exome sequencing (WES). A homozygous deletion of NPHP1 (1-20 exons) was found in both affected patients, which was further confirmed by quantitative PCR. Conclusions Homozygous full gene deletion of the NPHP1 gene was identified in a Chinese family with NPHP, which was the molecular pathogenic basis of this disorder. Furthermore, identification of the pathogenic genes for those affected patients can help to have a full knowledge on NPHP's molecular mechanism and precise treatment.